2013
DOI: 10.1002/ajmg.b.32147
|View full text |Cite
|
Sign up to set email alerts
|

Sex dependent influence of a functional polymorphism in steroid 5‐α‐reductase type 2 (SRD5A2) on post‐traumatic stress symptoms

Abstract: A non-synonymous, single nucleotide polymorphism (SNP) in the gene coding for steroid 5-α-reductase type 2 (SRD5A2) is associated with reduced conversion of testosterone to dihydrotestosterone (DHT). Because SRD5A2 participates in the regulation of testosterone and cortisol metabolism, hormones shown to be dysregulated in patients with PTSD, we examined whether the V89L variant (rs523349) influences risk for post-traumatic stress disorder (PTSD). Study participants (N = 1,443) were traumatized African-American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 79 publications
2
17
0
Order By: Relevance
“…We also compiled a list of genes that have been reported in the literature to be significantly associated with PTSD, either showing a main effect for the genetic marker, and/or a significant GxE interaction (Amstadter et al, 2009(Amstadter et al, , 2011Binder et al, 2008;Boscarino et al, 2011;Cao et al, 2013;Comings et al, 1996;Dragan and Oniszczenko, 2009;Gillespie et al, 2013;Goenjian et al, 2012;Grabe et al, 2009;Guffanti et al, 2013;Hauer et al, 2011;Kolassa et al, 2010;Logue et al, 2013a,b;Lyons et al, 2013;Mellman et al, 2009;Nelson et al, 2009;Ressler et al, 2011;Segman et al, 2002;Solovieff et al, 2014;Voisey et al, 2010;Wilker et al, 2013;Xie et al, 2013). Since most studies were performed in subjects of either European or African descent, we used these specific ancestry groups for comparison with MRS. We found that most of the 25 candidate genes showed nominally significant associations in MRS for at least one of the SNPs tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also compiled a list of genes that have been reported in the literature to be significantly associated with PTSD, either showing a main effect for the genetic marker, and/or a significant GxE interaction (Amstadter et al, 2009(Amstadter et al, , 2011Binder et al, 2008;Boscarino et al, 2011;Cao et al, 2013;Comings et al, 1996;Dragan and Oniszczenko, 2009;Gillespie et al, 2013;Goenjian et al, 2012;Grabe et al, 2009;Guffanti et al, 2013;Hauer et al, 2011;Kolassa et al, 2010;Logue et al, 2013a,b;Lyons et al, 2013;Mellman et al, 2009;Nelson et al, 2009;Ressler et al, 2011;Segman et al, 2002;Solovieff et al, 2014;Voisey et al, 2010;Wilker et al, 2013;Xie et al, 2013). Since most studies were performed in subjects of either European or African descent, we used these specific ancestry groups for comparison with MRS. We found that most of the 25 candidate genes showed nominally significant associations in MRS for at least one of the SNPs tested.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focused on: (1) the hypothalamic-pituitary-adrenal (HPA) axis, (2) the ascending brainstem locus coeruleus noradrenergic system, and (3) the limbic amygdalar frontal pathway mediating fear processing. Among the over 25 PTSD candidate genes currently reported (Amstadter et al, 2009(Amstadter et al, , 2011Binder et al, 2008;Boscarino et al, 2011;Cao et al, 2013;Comings et al, 1996;Dragan and Oniszczenko, 2009;Gillespie et al, 2013;Goenjian et al, 2012;Grabe et al, 2009;Guffanti et al, 2013;Hauer et al, 2011;Kolassa et al, 2010;Logue et al, 2013a,b;Lyons et al, 2013;Mellman et al, 2009;Nelson et al, 2009;Ressler et al, 2011;Segman et al, 2002;Solovieff et al, 2014;Voisey et al, 2010;Wilker et al, 2013;Xie et al, 2013), promising findings include associations of PTSD symptoms with the serotonin transporter gene (SERT, SLC6A4) (Xie et al, 2009), which is linked to depression and anxiety disorders, as well as differential acquisition of conditioned fear and increased amygdala excitability in humans. In addition, FKBP5, a co-chaperone of the glucocorticoid receptor involved in the HPA axis, has a significant interaction with severity of child abuse in the prediction of adult PTSD symptoms, indicating a gene by environment (GxE) interaction (Binder et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Note that 5alpha reductase is also involved in the production of GABAergic reduced metabolite of progesterone (e.g. allopregnanolone) and testosterone (androsterone), both considered to have a conceivable role in PTSD risk (Gillespie et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in vitro ORL 1 receptor activation blocks calcium channels and reduces intraneuronal cAMP and MAPK signaling, 72 which plays a major role in neuropathic pain. 62 Tolerance to opiates is thought to be mediated by increases in cAMP, 63 and at least in the case of m-opioid receptor tolerance, depends on calcium calmodulin-dependent adenylyl cyclase (ADC) 8-the activity of which is also essential for consolidation of fear conditioned learning. 73 Perhaps then, a deficit in ORL 1 signaling facilitates opiateresistant CP as well as comorbid PTSD.…”
Section: Opioid and Endocannabinoid System Considerations In Chronic mentioning
confidence: 99%